2022
DOI: 10.3390/en15041531
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Cleaning Performance of a Venturi Scrubber

Abstract: Industrial applications need to use different systems for the problem of gas cleaning. A lot of processes have been developed, such as the use of a venturi for gas cleaning and pollution reduction. Additionally, several studies have been developed especially in terms of pressure drop because it is one of the main parameters to determine its efficiency. While the phenomenon of mass transfer in a venturi scrubber has not found much attention, in the present study, a mass transfer two-dimensional simulation is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The comparisons made for velocity and pressure distributions found by Ref. [15] are shown in Fig. 3 and 4, respectively for two different gas velocities (10 and 15 m/s) and one mass flow rate of liquid of 0.02 kg/s.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The comparisons made for velocity and pressure distributions found by Ref. [15] are shown in Fig. 3 and 4, respectively for two different gas velocities (10 and 15 m/s) and one mass flow rate of liquid of 0.02 kg/s.…”
Section: Resultsmentioning
confidence: 95%
“…Prior to the parametric studies, the validation of the model is done with available data [15] found in the open literature. The comparisons made for velocity and pressure distributions found by Ref.…”
Section: Resultsmentioning
confidence: 99%